(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The goal of this study is to reveal the role and importance of using animation movies in the English classroom. In order to reach the goal of the present study, the following hypothesis has been provided: According to statistical significance, there are no differences between the mean degrees of the two groups (experimental group and control group). The experimental group was taught according to using animation movies, and the control group was taught according to the traditional method. The study has selected 61 students from the second-year class/English department/College of Education for Human Science/University of Diyala for the years 2018-2019. The sample has been divided into two groups: 30 students for the experimental group and 31 for the control group. The two groups are the same according to a statistical manipulation of a number of variables like education, age, and parents. Pretest and posttest are designed, and the validity of the tests and lesson plan have been obtained. The result of the test shows that there are statistical differences for both groups, and the best scores were for the benefit of the experimental group in the post-test.